The effect of different doses of estrogen to prevent adhesion recurrence after hysteroscopic lysis in Asherman's syndrome: A randomized clinical trial study - Leili Hafizi; Seyedeh Azam Pourhoseini; Golrokh Sherafati; Mona Jafari (Mashhad University of Medical Sciences, 2024)
Introduction: Intrauterine adhesion is a condition that can lead to infertility, amenorrhea, repeated abortion in the patient, and the treatment of these patients is usually associated with many challenges. The present study was performed with aim to compare the effect of two different doses of estrogen to prevent the recurrence of adhesions after hysteroscopic lysis in Asherman's syndrome. Methods: This randomized controlled clinical trial study was performed on 30 patients with moderate and severe Asherman's syndrome in Imam Reza Hospital of Mashhad, 2017-2021. Patients underwent hysteroscopy to remove adhesions. For all patients, an intrauterine balloon was placed after the operation and then they were treated with estrogen for 30 days and medroxyprogesterone 10 mg daily for the last 10 days. Patients were randomly assigned to two groups of estrogen 2.5 mg and 5 mg daily. After the end of the treatment period, with hysteroscopy again, the state of the uterine cavity was checked and the response to the treatment was compared in terms of the return of adhesions and its intensity in the two groups. Data were analyzed using SPSS software (version 26) and Shapiro-Wilk and Mann-Whitney U statistical tests. P<0.05 was considered statistically significant. Results: The most common cause of Asherman in the 2.5 mg group was curettage (60%) and in the 5 mg group, other surgeries (60%). The two groups had no statistically significant difference in terms of confounding variables including age, cause of Asherman's disease and severity of adhesions (p=0.714). In examining the response to treatment, there was no statistically significant difference between the two groups in terms of adhesion severity in repeated hysteroscopy (p=0.858) and response to treatment (p=0.714). Conclusion: For the prevention of recurrence of intrauterine adhesions (Asherman's syndrome) after hysteroscopic lysis of adhesions, the dose of 2.5 mg of Conjugated estrogen was as effective as the dose of 5 mg of estrogen.